Synergistic actions of olomoucine and bone morphogenetic protein-4 in axonal repair after acute spinal cord contusion - Chen, Liang (Neural Regen Res, 2014)
To determine whether olomoucine acts synergistically with bone morphogenetic protein-4 in the treatment of spinal cord injury, we established a rat model of acute spinal cord contusion by impacting the spinal cord at the T(8) vertebra. We injected a suspension of astrocytes derived from glial-restricted precursor cells exposed to bone morphogenetic protein-4 (GDAs(BMP)) into the spinal cord around the site of the injury, and/or olomoucine intraperitoneally. Olomoucine effectively inhibited astrocyte proliferation and the formation of scar tissue at the injury site, but did not prevent proliferation of GDAs(BMP) or inhibit their effects in reducing the spinal cord lesion cavity. Furthermore, while GDAs(BMP) and olomoucine independently resulted in small improvements in locomotor function in injured rats, combined administration of both treatments had a significantly greater effect on the restoration of motor function. These data indicate that the combined use of olomoucine and GDAs(BMP) creates a better environment for nerve regeneration than the use of either treatment alone, and contributes to spinal cord repair after injury.